Detection of Nosema spp. spore contamination in commercial Apis mellifera bee pollens of Thailand. Issue 4 (8th August 2017) - Peukpiboon, Thitiporn; Benbow, Mark Eric; Suwannapong, Guntima
Abstract : Currently, there is widespread concern about declining honey bee populations affected by Nosema ceranae and Nosema apis, because infection by these pathogens may result in a reduction of pollination services and therefore raise concerns about pollination shortages. We investigated Nosema spp. spore contamination in Apis mellifera bee pollen samples from 34 apiaries in three different regions of Thailand. Nosema spp. spores were detected using light microscopy, and species identification using molecular characterization of the 16S rRNA gene. The numbers of Nosema spp. spores/gram bee pollen were significantly different among all sources of pollen samples ( F 32 = 948.52, p ≤ 0.001). The highest spore contamination was found in pollen sample from Phrae province, while the lowest was found in samples from Nong Bua Lam Phu and Chumporn provinces. In total, pollen samples of 26 apiaries were positive for N. ceranae, the product size was 145 bp, while only one sample from an apiary in Chiang Mai province was positive for both N. apis (the product size was 226 bp) and N. ceranae . No Nosema spores were found in pollen samples from the remaining seven apiaries. The different regions had differences in both numbers and species of bee plants, with 27 species identified, and 15 species that did not match local reference plants. The major bee plants identified from the surveyed bee pollen were Mimosa diplotricha and Mimosa pudica . The different plant species showed differences in the amount of spore contamination. In particular pollen samples containing M. diplotricha together with Z. mays L. showed the highest contamination.